Economese for beginners - Cantos, Jessica Reyes (Published by Philippine Center for Policy Studies and Documentation for Action Groups in Asia, 1994)
This mini-list is intended to help today's activists,leaders of people organizations and social movements grapple with common sense economic terms. It emphasizes on free market and structural adjustment terms. Includes charts, graphs, statistics and caricature.